Association between C-reactive protein-albumin-lymphocyte (CALLY) index and cerebral edema in acute ischemic stroke patients: - Mutlucan, Umut Ogün; Bedel, Cihan; Selvi, Fatih; Zortuk, Ökkeş; Türk, Cezmi Çağrı (Vojnosanitetski pregled, 2025)
Background/Aim. There is an association between brain edema and inflammation that may occur in a stroke. The aim of the study was to determine the relationship between the C-reactive protein-albumin-lymphocyte (CALLY) index and cerebral edema developed as a consequence in stroke patients. Methods. The retrospective study included patients aged 18 years and above who presented to the emergency department from January 2021 to December 2023 and were admitted to the neurology/intensive care unit with a diagnosis of stroke. The following hematological parameters were included in the research: the pan-immune-inflammation value (PIV), systemic inflammatory response index (SIRI), systemic immune-inflammation index (SII), and the CALLY index. These parameters were calculated from blood samples of patients taken during admission, and neurosurgeons assessed the development of cerebral edema and the need for decompression. The parameters were compared between two groups of patients: the surgical group (SG), with patients in need of decompression, and the nonsurgical group (NSG), with patients who do not have such a need. Results. The study included 274 patients in total, of which 189 (68.90%) were in NSG and 85 (31.10%) in SG. It was found that the CALLY index was significantly higher in patients in NSG than in patients in SG (16.47 vs. 0.79; p < 0.001). SIRI and SII levels were significantly higher in SG patients compared to NSG (p < 0.001 and p = 0.001, respectively). PIV level was also significantly higher in SG than in NSG (p < 0.001). At a cut-off value of 4.06, the CALLY index had a sensitivity of 69.40% and a specificity of 83.00%. Conclusion. The CALLY index is an easily accessible and calculable marker, which can be used to predict the need for decompression that may develop in stroke patients.
Keywords: brain edema; c-reactive protein; hematologic tests; stroke